UPAYA MENINGKATKAN Produktivitas Miselium - Lukas S. Budipramana1; Gatot Suparno1; Isnawati1; Igm Sanjaya2 (Matematika dan Sains, 2010)
The aim of the research is to know the natural material which can we use to grow the mycelium and fruit body of tiram putih mushroom (Pleurotus ostreatus). There are three kinds of media in this research, namely the straw, the sawmill powder, and the stem of an ear of corn. The mycelium of tiram putih mushroom could grow in the three kinds of media but the growth acceleration was different. The mycelium of tiram putih mushroom had the best growth acceleration in the sawmill powder media, number two in stem of an ear of corn media and then the straw media. The fruit body production in the straw media was better than that in the sawmill powder media.